Do thermoregulatory costs limit altitude distributions of Andean forest birds? (2017)
Along tropical mountains, species often occupy narrow altitude ranges. Numerous biotic and abiotic factors have been proposed as determinants of altitude occupancy. We measured several aspects of thermal physiology of 215 bird species across a 2·6-km altitude gradient in the Peruvian Andes. We predicted that highland species would show adaptation to the colder high-altitude climate and that energy costs of thermoregulation might limit upslope dispersal of lowland natives. We found reductions in thermal conductance, body temperature and lower critical temperature in highland birds compared with lowland species. These combine to make highland natives more resistant to heat loss. We did not find convincing evidence that acute thermal limits or energy costs of thermoregulation constrained altitude distributions.